2010
DOI: 10.1007/s10529-010-0270-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface display of active lipase in Pichia pastoris using Sed1 as an anchor protein

Abstract: A Pichia pastoris cell-surface display system was constructed using the Sed1 anchor system that has been developed in Saccharomyces cerevisiae. Candida antarctica lipase B (CALB) was used as the model protein and was fused to an anchor that consisted of 338 amino acids of Sed1. The resulting fusion protein CALBSed1 was expressed under the control of the alcohol oxidase 1 promoter (pAOX1). Immunofluorescence microscopy of immunolabeled Pichia pastoris revealed that CALB was displayed on the cell surface. Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…The disruption of GAS1 in P. pastoris production strains for obtaining human trypsinogen and human serum albumin did not result in an enhancement of product secretion, whereas Rhizopus oryzae lipase secretion could be improved 2-fold (17). In addition, GPI-modified cell wall proteins from S. cerevisiae, such as ␣-agglutinin, Tip1p, Flo1p, and Sed1p, have been used as anchor proteins for P. pastoris cell surface display of heterologous proteins (18)(19)(20). However, very few endogenous GPImodified cell wall proteins of P. pastoris have been confirmed and used in P. pastoris cell surface display.…”
mentioning
confidence: 99%
“…The disruption of GAS1 in P. pastoris production strains for obtaining human trypsinogen and human serum albumin did not result in an enhancement of product secretion, whereas Rhizopus oryzae lipase secretion could be improved 2-fold (17). In addition, GPI-modified cell wall proteins from S. cerevisiae, such as ␣-agglutinin, Tip1p, Flo1p, and Sed1p, have been used as anchor proteins for P. pastoris cell surface display of heterologous proteins (18)(19)(20). However, very few endogenous GPImodified cell wall proteins of P. pastoris have been confirmed and used in P. pastoris cell surface display.…”
mentioning
confidence: 99%
“…A few other studies have reported that cell surface display of enzymes can improve thermostability compared with purified enzymes. For example, Sed1 and Cwp2 are utilized as the anchor proteins to fuse lipase for surface display in Pichia pastoris and Saccharomyces cerevisiae, respectively [19,27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is also a suitable host for use in large-scale fermentation cultures for molecular display technology. Both N-and C-terminusfree display systems of P. pastoris have been established using cell wall proteins -agglutinin, a-agglutinin, Flo1p, Sed1p, and Tip1p from S. cerevisiae, as described above Su et al, 2010;Tanino et al, 2006 .…”
Section: Molecular Display Technology Using Pichia Pastorismentioning
confidence: 99%